Fermionic boundary conditions and the finite temperature transition of QCD - Bilgici, Erek; Bruckmann, Falk; Danzer, Julia; Gattringer, Christof; Hagen, Christian; Ilgenfritz, Ernst-Michael; Maas, Axel Torsten (Few-body systems, 2010)
Finite temperature lattice QCD is probed by varying the temporal boundary conditions of the fermions. We develop the emerging physical behavior in a study of the quenched case and subsequently present first results for a fully dynamical calculation comparing ensembles below and above the phase transition. We show that for low temperature spectral quantities of the Dirac operator are insensitive to boundary conditions, while in the deconfined phase a non-trivial response to a variation of the boundary conditions sets in.